PENGARUH PAJAK TERHADAP TRANSFER PRICING DENGAN KEPEMILIKAN ASING SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Desi Puspita Rini (Fakultas Ekonomi UNIBBA, 2021)
This study aims to examine the effect of taxes on transfer pricing with foreign ownership as a moderating variable. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange Bursa Efek Indonesia (BEI) 2016-2019. Sampling using purposive sampling method and obtained 13 companies. This study uses multiple regression analysis and Moderated Regression Analysis (MRA). The results showed that tax had no effect on transfer pricing. Foreign ownership is unable to moderate the influence of tax on transfer pricing